Does primary school duration matter? Evaluating the consequences of a large Chinese policy experiment. (June 2019) - Eble, Alex; Hu, Feng
Abstract: Nearly all governments provide primary schooling, but surprisingly little is known about how changes to the duration of primary school affect educational attainment and performance in the labor market. We study a Chinese policy which extended the duration of primary school from five years to six but did not change the curriculum. We exploit its gradual rollout over space and time to generate causal estimates of its impact on educational attainment and subsequent labor market outcomes. We find that the policy has small, largely positive effects on post-primary educational attainment, and raises average monthly income by 2.6%. The policy is progressive, generating higher returns (5–8%) among both women and the least educated. We estimate the policy has already reallocated 450 million years of labor from work to schooling and we generate cost-benefit estimates to quantify this tradeoff, highlighting the large public finance implications of this policy decision.